EVALUATION OF IT GOVERNANCE BASED ON SPBE USING COBIT 2019 AND ISO/IEC 38500:2015 - Arta Perdana, Bagus Gede; Muhammad, Alva Hendi; Nasiri, Asro (Jurnal Inovtek Polbeng Seri Informatika, 2024)
SPBE is a mandatory IT Governance framework implemented by all government agencies in Indonesia. Since its implementation in 2018, the national average maturity level remains very low, with the main obstacle being in the fundamental domain of IT Governance, as identified during the 2022 evaluations. An evaluation was conducted on government agencies facing similar challenges using COBIT 2019 as the framework, providing the best practices and widely used standards for IT Governance. This was combined with the principles of ISO/IEC 38500:2015, an international standard for IT Governance. Maturity level measurements were taken to assess the current conditions of the agencies and provide improvement recommendations linked to indicators in the SPBE maturity level evaluation guidelines. The improvement recommendations provided were able to enhance maturity levels holistically, not only in the IT Governance domain but across the entire management processes and product services of the agencies, aiming to achieve sustainable benefits and objectives.